Объяснение:
x²-12x+32=(x-8)(x-4) - открываешь скобки
x²-12x+32=x²-8x-4x+32
x²-12x+32-x²+8x+4x-32=0
все сокращается, следовательно тождество верное
0=0
Ответ:
x²-12x + 32 = (x – 8) (x – 4)
L=x²+12x+32
P=(x-8)(x-4)=x²-4x-8x+32=x²-12x+32
L=P
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
x²-12x+32=(x-8)(x-4) - открываешь скобки
x²-12x+32=x²-8x-4x+32
x²-12x+32-x²+8x+4x-32=0
все сокращается, следовательно тождество верное
0=0
Ответ:
Объяснение:
x²-12x + 32 = (x – 8) (x – 4)
L=x²+12x+32
P=(x-8)(x-4)=x²-4x-8x+32=x²-12x+32
L=P